Foodborne Illness Outbreaks at Retail Food Establishments -- National Environmental Assessment Reporting System, 25 State and Local Health Departments, 2017-2019. - Moritz, Erin D.; Delrahim Ebrahim-Zadeh, Shideh; Wittry, Beth; Holst, Meghan M.; Daise, Bresa; Zern, Adria; Taylor, Tonia; Kramer, Adam; Brown, Laura G. (MMWR Surveillance Summaries, 2023)
Problem/Condition: Each year, state and local public health departments report hundreds of foodborne illness outbreaks associated with retail food establishments (e.g., restaurants or caterers) to CDC. Typically, investigations involve epidemiology, laboratory, and environmental health components. Health departments voluntarily report epidemiologic and laboratory data from their foodborne illness outbreak investigations to CDC through the National Outbreak Reporting System (NORS); however, minimal environmental health data from outbreak investigations are reported to NORS. This report summarizes environmental health data collected during outbreak investigations and reported to the National Environmental Assessment Reporting System (NEARS). Period Covered: 2017-2019. Description of System: In 2014, CDC launched NEARS to complement NORS surveillance and to use these data to enhance prevention efforts. State and local health departments voluntarily enter data from their foodborne illness outbreak investigations of retail food establishments into NEARS. These data include characteristics of foodborne illness outbreaks (e.g., etiologic agent and factors contributing to the outbreak), characteristics of establishments with outbreaks (e.g., number of meals served daily), and food safety policies in these establishments (e.g., ill worker policy requirements). NEARS is the only available data source that collects environmental characteristics of retail establishments with foodborne illness outbreaks. Results: During 2017--2019, a total of 800 foodborne illness outbreaks associated with 875 retail food establishments were reported to NEARS by 25 state and local health departments. Among outbreaks with a confirmed or suspected agent (555 of 800 [69.4%]), the most common pathogens were norovirus and Salmonella, accounting for 47.0% and 18.6% of outbreaks, respectively. Contributing factors were identified in 62.5% of outbreaks. Approximately 40% of outbreaks with identified contributing factors had at least one reported factor associated with food contamination by an ill or infectious food worker. Investigators conducted an interview with an establishment manager in 679 (84.9%) outbreaks. Of the 725 managers interviewed, most (91.7%) said their establishment had a policy requiring food workers to notify their manager when they were ill, and 66.0% also said these policies were written. Only 23.0% said their policy listed all five illness symptoms workers needed to notify managers about (i.e., vomiting, diarrhea, jaundice, sore throat with fever, and lesion with pus). Most (85.5%) said that their establishment had a policy restricting or excluding ill workers from working, and 62.4% said these policies were written. Only 17.8% said their policy listed all five illness symptoms that would require restriction or exclusion from work. Only 16.1% of establishments with outbreaks had policies addressing all four components relating to ill or infectious workers (i.e., policy requires workers to notify a manager when they are ill, policy specifies all five illness symptoms workers need to notify managers about, policy restricts or excludes ill workers from working, and policy specifies all five illness symptoms requiring restriction or exclusion from work). Interpretation: Norovirus was the most commonly identified cause of outbreaks reported to NEARS, and contamination of food by ill or infectious food workers contributed to approximately 40% of outbreaks with identified contributing factors. These findings are consistent with findings from other national outbreak data sets and highlight the role of ill workers in foodborne illness outbreaks. Although a majority of managers reported their establishment had an ill worker policy, often these policies were missing components intended to reduce foodborne illness risk. Contamination of food by ill or infectious food workers is an important cause of outbreaks; therefore, the content and enforcement of existing policies might need to be re-examined and refined.